Preparation of 3-Alkyl-Substituted 1-Alkoxyallenes – Synthetic and Mechanistic Aspects - Hausherr, Arndt; Reissig, Hans-Ulrich (Synthesis, 2018)
Two routes to 3-alkyl-substituted 1-alkoxyallenes are investigated. The deprotonation and alkylation at C-3 of methoxyallene requires prior silylation at C-1 and provides mixtures of the expected products and 1-alkyl-substituted methyl propargyl ethers as minor component. The desilylation of these mixtures affords the desired 3-alkyl-substituted 1-methoxyallenes together with the 1-alkyl-substituted isomers in moderate overall yields. Following the second route, the disadvantages of this three-step method are avoided. In analogy to Brandsma, C-3 alkylation of methyl propargyl ether and subsequent isomerization under basic conditions affords two of the desired 3-alkyl-substituted methoxyallenes in good yields. This method is also applied to propargyl ethers bearing a diacetone-fructose-derived auxiliary. Two diastereomeric 3-alkyl-substituted 1-alkoxyallenes are formed during the isomerization, the ratio being strongly dependent on the reaction conditions. The mechanistic aspects of these observations are discussed on the basis of deuteration experiments and the configurational stability of the ambident propargyl-allenyl carbanion involved.
Keywords: alkoxyallenes; alkynes; lithiation; alkylation; carbohydrate derivatives